The Effect of obesity and weight loss through calorie restriction on HDL function - Moradi, Masoumeh; Alvandi, Ehsan; Koohdani, Fariba (Progress in Nutrition, 2019)
The aim of the present study is to conduct a literature review on the mechanisms responsible for altered high density lipoprotein (HDL) in obesity and the effect of weight loss by calorie restriction on HDL function. Obesity, as a major modifiable risk factor for coronary heart disease (CHD), can influence the concentration and function of lipoproteins in plasma. HDL is associated inversely with CHD and acts through its antioxidant and anti-inflammatory capacity, as well as stimulation of reverse cholesterol transport from extrahepatic tissues to the liver for excretion into the bile. HDL structure and function is linked to its major apolipoproteins (APO) including APO A-I and APO A-II, and its related enzymes such as paraoxonase (PON) that cotransport with HDL in plasma and lecithin: cholesterol acyltransferase (LCAT) which contributes to HDL maturation. Through production of various cytokines which leads to inflammation, obesity can affect these factors and changes their serum levels as well as their function. In this article, the mechanism responsible for altered HDL in obesity and the effect of weight loss by calorie restriction, as the most commonly used therapy for obesity, on HDL concentration and its function will be reviewed.